HEMATOLOGICAL AND BIOCHEMICAL INDICATORS OF CATS AND DOGS IN CASE OF CTENOCEPHALOSIS - Kruchynenko, O. V.; Brydykhina, A. Yu. (Scientific Progress & Innovations, 2020)
Ctenocephalosis is the most wide-spread external parasitic disease of cats and dogs caused by fleas of Ctenocephalides (C. W. Stiles & B. J. Collins, 1930) genus. One of peculiarities of the invasion is its chroni-cal development connected with constant attack of fleas on animal and characterized by itching, appearing alopecia, developing exzemas, dermatites, and so on. Quite often in case of Ctenocephalides spp. parasitiz-ing, allegic dermatitis, ferrum-deficit anemia, and imaciation of infected animal are registered. The studies were conducted in the laboratory of the Department of parasitology and veterinary-sanitary expert examina-tion of Poltava State Agrarian Academy and in the veterinary clinic of “Bio-center” Ltd (in the town of Pol-tava). The aim of the research was to find out the effect of Ctenocephalides spp. external parasites on hema-tological and biochemical indices of blood serum in infected cats and dogs. Animals having the index of in-fection intensity from 17 to 42 specimens of insects on the animal body were taken for the experiments. The following indicators were determined in the animals’ blood: the amount of leukocytes, erythrocytes, the con-tent of hemoglobin, lymphocytes, monocytes, eosinophiles, basophils and immature cells, granulocytes, and hematocrite. Four groups of animals were formed: two control (clinically healthy cats and dogs) and two experimental ones (infected with Ctenocephalides spp. parasitic insects). According to the study results, it has been found that blood-sucking insects negatively affect the organism of diseased animals. The apparent decrease in the amount of erythrocytes (Р<0.05), hemoglobin (Р<0.01) and hematocryte content was regis-tered in the blood of infected animals. At the same time, the index of leukocyte amount increased in the blood of diseased cats and dogs (Р<0.01). The following indicators were determined in the blood serum of the dis-eased animals: the content of total protein, creatinine, urea, glucose, the activity of alanineaminotransferase, aspartate aminotransferase, and alkali phosphatase. As a result of the conducted studies, it has been revealed that changes in the blood serum biochemical indices showed the presence of concomitant pathology – hepatorenal syndrome, manifested by the increase in total protein, urea, creatinine, and also the activity of alanine aminotransferase, aspartate aminotransferase, and alkali phosphatase (Р<0.01). The obtained results of experimental data expand the known information as to pathogenesis of fleas parasitizing on cats and dogs, and also allow to conduct effectively the treatment of diseased animals.